A critical assessment of sympathetic restraint in submaximal exercise: Implications for integrated cardiovascular circuit control in exercise - Patrick J. Drouin; Stacey P. A. Forbes; Abby K. Zedic; Stuart P. S. Mladen; Michael E. Tschakovsky (Experimental Physiology)
Abstract Sympathetic restraint in exercising muscle is currently viewed as required to prevent ‘excess’ vasodilatation from exceeding the cardiac output (Q̇) response, even in submaximal exercise. Certainly, muscle vasodilatory capacity dictates the requirement for sympathetic restraint when cardiac pumping capacity is approached. However, a similar role in submaximal exercise has at least two important implications for integrated cardiovascular control in exercise that have not been considered. First, such a role means that there is a ‘set’ Q̇ response to a given exercise challenge that dictates the cardiovascular circuit flow and therefore the vasodilatation allowed such that Q̇–peripheral blood flow balance and target arterial blood pressure are achieved. This represents a ‘cardiocentric’ model of integrated cardiovascular control, whereby the heart leads and the peripheral resistance vessel tone is modulated accordingly. Second, what is commonly described as ‘tight’ matching of exercising muscle oxygen delivery relative to demand would therefore require that the Q̇ response is closely ‘calibrated’ to exercising muscle metabolic demand. This would require a means of driving cardiac activation via precise communication of exercising muscle metabolic demand. However, considerable evidence demonstrates that ‘excess’ vasodilatation in a healthy system simply leads to a matching increased Q̇ without arterial blood pressure compromise. This review re‐examines the evidence for existence of sympathetic restraint in exercising muscle and its currently proposed role. We propose that key questions remain unanswered and that renewed investigation into sympathetic restraint and its role can lead to important advances in understanding integrated cardiovascular control in exercise.